2016
DOI: 10.1123/jpah.2015-0050
|View full text |Cite
|
Sign up to set email alerts
|

Group Physical Activity Intervention for Childhood Cancer Survivors: A Pilot Study

Abstract: Increases in MVPA can be seen in childhood cancer survivors who participate in a group intervention that includes support of self-efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Future work should draw upon previous findings that have shown efficacy in this population, including the use of biochemical verification in tobacco interventions; assisting with decision making related to substance use; and using Web sites, videogames, and other electronic formats to encourage healthy eating. Designing physical activity interventions that use group exercise or increase self‐efficacy as well as promoting ecologic/environmental interventions, such as active transportation and adventure‐based training, are areas to explore. Interventions that target alcohol use, sunscreen behavior, and risky sexual behavior are limited and require further investigation.…”
Section: Health Behaviorsmentioning
confidence: 99%
“…Future work should draw upon previous findings that have shown efficacy in this population, including the use of biochemical verification in tobacco interventions; assisting with decision making related to substance use; and using Web sites, videogames, and other electronic formats to encourage healthy eating. Designing physical activity interventions that use group exercise or increase self‐efficacy as well as promoting ecologic/environmental interventions, such as active transportation and adventure‐based training, are areas to explore. Interventions that target alcohol use, sunscreen behavior, and risky sexual behavior are limited and require further investigation.…”
Section: Health Behaviorsmentioning
confidence: 99%
“…7,[9][10][11][12] Healthy lifestyle behaviors, such as regular physical activity (PA) and healthier eating behaviors, can help reduce risk of these negative late effects. [11][12][13][14] However, these healthy behaviors might be especially difficult for PCS and their families to implement, particularly because during treatment, PA and healthy eating behaviors decline dramatically. 15 Consequently, families have great difficulty reversing these behaviors posttreatment.…”
Section: Introductionmentioning
confidence: 99%
“…Overwhelming evidence indicates overweight and obesity increase longer term health risks associated with pediatric cancer, such as cardiac and endocrine functioning and bone health . Healthy lifestyle behaviors, such as regular physical activity (PA) and healthier eating behaviors, can help reduce risk of these negative late effects . However, these healthy behaviors might be especially difficult for PCS and their families to implement, particularly because during treatment, PA and healthy eating behaviors decline dramatically .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies conducted in Western countries have shown that PA interventions are acceptable, safe, and potentially beneficial during treatment in pediatric patients with cancer . Additionally, a group‐based exercise program could improve patients’ self‐confidence, promote their adherence, relieve their negative emotions, and increase their motivation to perform PA by promoting social support . More importantly, PA health education provided by professionals could improve patients’ PA levels because such consultation helps patients and caregivers ensure the safety and benefits of PA and change patients’ and caregivers’ perspectives .…”
Section: Introductionmentioning
confidence: 99%